Communication Pattern of Tripusat Education in Developing the Qur'anic Character of Students at State Junior High School 1 Camplong - Muhammad Robby (International Journal of Islamic Educational Research, 2025)
This research aims to provide a description of the communication phenomenon that occurs between students and parents, students and teachers, and students and the community environment. The research is motivated by the misconduct of students such as truancy, lying, and frequent prayer. This study uses a qualitative approach. Data were collected through observations, interviews, and documentation. Data analysis was conducted by data collection, data reduction, presenting data in textual form, and verification leading to data conclusion. The results of the research show that: 1) The implementation of a good three center communication in education is crucial to maintaining the Qur'anic character of students, as various factors such as religious, socio-economic, and stakeholders' communication understanding influence students' character; 2) Students receive good guidance at school, moderately at home, and inadequately at the surrounding environment, thus the communication concept to foster Qur'anic character does not run optimally. This research provides important contributions in the field of fostering Qur'anic character, particularly in SMP Negeri 1 Camplong. The conclusion of this research is that the role of family and the environment greatly influences the process of fostering the Qur'anic character of students. The importance of this role is vital in conscious efforts to improve students' Qur'anic character.